India sweets and spices [videorecording (DVD)] - Ali, Sophia, 1995-; Koirala, Manisha; Hussain, Adil (Decal, 2022)
A young Indian woman returns to her wealthy hometown and faces her pretentious family and their traditions. But when she meets the handsome son of local shopkeepers and invites him over, she accidentally uncovers a pair of family secrets.